Schizophrenia patients with high intelligence: A clinically distinct sub-type of schizophrenia? - Černis, E; Vassos, E; Brébion, G; McKenna, P; Murray, R; David, A; Maccabe, J (Elsevier, 2015)
Background: Schizophrenia patients are typically found to have low IQ both pre- and post-onset, in comparison to the general population. However, a subgroup of patients displays above average IQ pre-onset. The nature of these patients’ illness and its relationship to typical schizophrenia is not well understood. The current study sought to investigate the symptom profile of high-IQ schizophrenia patients. Methods: We identified 29 schizophrenia patients of exceptionally high pre-morbid intelligence (mean estimated pre-morbid intelligence quotient (IQ) of 120), of whom around half also showed minimal decline (less than 10 IQ points) from their estimated pre-morbid IQ. We compared their symptom scores (SAPS, SANS, OPCRIT, MADRS, GAF, SAI-E) with a comparison group of schizophrenia patients of typical IQ using multinomial logistic regression. Results: The patients with very high pre-morbid IQ had significantly lower scores on negative and disorganised symptoms than typical patients (RRR = 0.019; 95% CI = 0.001, 0.675, P = 0.030), and showed better global functioning and insight (RRR = 1.082; 95% CI = 1.020, 1.148; P = 0.009). Those with a minimal post-onset IQ decline also showed higher levels of manic symptoms (RRR = 8.213; 95% CI = 1.042, 64.750, P = 0.046). Conclusions: These findings provide evidence for the existence of a high-IQ variant of schizophrenia that is associated with markedly fewer negative symptoms than typical schizophrenia, and lends support to the idea of a psychosis spectrum or continuum over boundaried diagnostic categories.